Approximate Inertial Manifolds to the Newton-Boussinesq Equations (Journal of Partial Differential Equations, 1996)
Approximate inertial manifolds are related to the study of long time behaviour of dissipative partial differential equa tions. In this paper, we construct two approximate inertial manifolds for the two dimensional Newton-Boussinesq Equations. The orders of approximations of these manifolds to the global attractor are derived.
Keywords: Nonlinear Galerkin methods; long time integration; approximate inertial manifolds; Newton-Boussinesq equations